(untitled) (REVISTA NODO, 2022)
In this essay I propose to open the concept of radio art in order to enrich it and to approach the different aesthetic styles of electroacústic music and sound art, because the radiophonic institutions and their protagonists have limited the definitions of radio art genres, limiting in this way the expressive possibilities of this interesting electric space. It is necessary to do a comparative analysis of the languages of these three fields (radio art, sound art and electroacoustic music) in order to find their convergences. From there, I am inviting radio artists to get closer to electroacoustic and conceptual art aesthetics to include in their works, and musicians and all kind of artists to make radio art. Finally, I do an historical analysis of the radiophonic and cultural institutions in Mexico in an international context, acknowledging their protagonist role in Latin America, and proposing an increased support for the creation and diffusion of sound works for the radio.